THE FORMATION OF THE SYSTEM OF MONITORING AND SELF-EVALUATION OF THE QUALITY OF STUDENTS ' LEARNING OUTCOMES IN UNIVERSITY - Polyakova, G.; Achkasova, S. (Continuing Professional Education: Theory and Practice, 2023)
This article draws attention to the fact that the construction and implementation of a quality assurance system in higher education should be based on the monitoring procedures and implementation on this basis of self-educational-cognitive activity of students and teaching activities scientific-pedagogical staff. Reveals the essential characteristics of the system of monitoring and self-evaluation of quality of learning outcomes, namely: goal, objectives, conditions, objects, indicators, tools, levels and procedures. The ways of forming monitoring and self-evaluation of the quality of outcomes. The purpose of forming the system of monitoring and self-evaluation of the quality of students ' learning outcomes is the construction of mechanisms and tools for self-government of subjects of the educational process at the faculty level, Department, teacher, student to provide quality training in a higher educational institution. The conditions of organization and conduct of monitoring and self-evaluation of quality of learning outcomes are: having a clear system of monitoring and evaluation of learning outcomes; maintaining a faculty e-journal of learning outcomes and attendance; ability to automate procedures. The objects of monitoring are the quality of learning outcomes, the quality of attendance by students. Monitoring and self-evaluation of quality of learning outcomes of students is carried out according to academic discipline, course, direction / specialty training; at the level of the student, the teacher, Department, faculty, University. The procedure for monitoring the quality of students ' learning outcomes has four cyclical stages: preparatory, practical, analytical, regulatory.